2012
DOI: 10.1590/s0103-21002012005000001
|View full text |Cite
|
Sign up to set email alerts
|

Preditores da Síndrome de Burnout em enfermeiros de serviços de urgência pré-hospitalar

Abstract: Objetivo: Analisar os preditores da Síndrome de Burnout apresentados por enfermeiros de serviços de urgência pré-hospitalar móvel. Métodos: Estudo descritivo, exploratório, quantitativo com 38 enfermeiros. Utilizou-se questionário estruturado acrescido do Maslach Burnout Inventory em setembro de 2010. Na análise dos dados, foram usadas técnicas de estatística descritiva e inferencial (teste t-Student e teste F (ANOVA)). A verificação da hipótese de igualdade foi realizada pelo teste F de Levene e a de normalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
3
20

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 7 publications
3
20
3
20
Order By: Relevance
“…Marriage or having a stable partner and having children is attributed to a lower propensity for chronic stress. (21) However, students who reported having at least one child presented 3.66 more chances of having stress.…”
Section: Discussionmentioning
confidence: 99%
“…Marriage or having a stable partner and having children is attributed to a lower propensity for chronic stress. (21) However, students who reported having at least one child presented 3.66 more chances of having stress.…”
Section: Discussionmentioning
confidence: 99%
“…A contradictory result was found for the variable age in the literature (16) , but most studies report that burnout has a higher prevalence among younger nurses, since these are considered inexperienced and more likely to suffer anxiety when faced with eventual intercurrences during their shift (17)(18) . A study carried out in Mato Grosso, in the Center-West of Brazil, with nursing workers, showed that 7.09% of the sample presented burnout and less than 5 years of working in the unit, that is, they had little professional experience in the ICU (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The fast pace of organizational, social, and legal transformations has affected the health/sickness process of workers (1) . Prolonged exposure to environmental and situational stressors leads to occupational stress, which can increase emotional exhaustion and depersonalisation, and reduce professional accomplishment (2) .…”
Section: Introductionmentioning
confidence: 99%
“…These workers are more susceptible to occupational stress due to their exhaustive and tense work (4) , which in time can lead to burnout and other mental disorders (6) . Burnout and stress are the most widely addressed subjects by researchers in the area of mental health for workers (1) . It has been reported that burnout is more common among nurses than other health workers (7) because of the stressful situations nurses experience at work and their direct contact with critically ill patients with different prognoses and varying degrees of suffering (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation